2007
DOI: 10.1021/cm0706393
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of 3D Dendritic Gold Nanostructures and Their Use as Substrates for Surface-Enhanced Raman Scattering

Abstract: Three-dimensional dendritic gold nanostructures (3D-DGNs) were prepared at room temperature through an aqueous/organic interfacial reaction of hydrogen tetrachloroaurate (HAuCl 4 , in aqueous phase) and 3,4-ethylenedioxythiophene (EDOT, in organic phase) without the use of any seeds, templates, surfactants, or stabilizers. SEM and TEM studies indicated that the 3D-DGNs compose of numerous nanowires with diameters around 30 nm and each wire brings a nanosheet head with thickness of 80 ( 5 nm. The effects of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
88
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 71 publications
5
88
1
Order By: Relevance
“…Recently, gold (Au) nanostructures have attracted great interest for their unique physicochemical properties and extensive applications in catalysis [1,2], SERS [3,4], and biomedical images [5,6]. It is known that the shape and size of Au nanocrystals have remarkable effects on their properties and applications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, gold (Au) nanostructures have attracted great interest for their unique physicochemical properties and extensive applications in catalysis [1,2], SERS [3,4], and biomedical images [5,6]. It is known that the shape and size of Au nanocrystals have remarkable effects on their properties and applications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, wet chemical strategy is employed to prepare dendritic Au nanostructures. Lu's group prepared three-dimensional (3D) dendritic Au nanostructures via an aqueous/organic interfacial reaction of HAuCl 4 and 3,4-ethylenedioxythiophene [3]. Qin and coworkers synthesized Au nanodendrites from the reaction between a zinc plate and HAuCl 4 in ionic liquid [21].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive investigations have demonstrated that the SERS enhancements of nanostructured Au and Ag strongly rely on their morphology, size, and assembly, and various nanostructured Au and Ag have been developed as sensitive SERS substrates. [17][18][19][20][21][22] However, amongst the three coinage metals, the SERS effect of nanostructured Cu is much less investigated. [23,24] This is probably due to their insignificant SERS effects and poor thermal and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…19 Numerous studies have demonstrated that EM field intensity can be greatly enhanced within the narrow gap between two metal NPs, and hence enormous SERS enhancements can be achieved for molecules locating in the gap area. [20][21][22][23] When two metal NPs are brought close to form an aggregated structure, their transition dipoles will couple to each other and their optical near-fields will coherently interfere at the junction site, resulting in the so-called plasmonic "hot" spots with large near-field enhancements. In general, there are several methods to induce NP aggregation, including chemically induced 24,25 and photoinduced effects, 26,27 be simply used to arrange or concentrate individual structures into controllable aggregation configuration, thus generating a favorable density of "hot" spots for subsequent SERS enhancements.…”
Section: Introductionmentioning
confidence: 99%